Technological Pedagogical Content Knowledge: Implementation of a Didactic Proposal for Preservice History Teachers - Ciriza-Mendívil, Carlos D.; Lacambra, Ana Mendioroz; Hernández de la Cruz, José M. (Frontiers in Education, 2022)
Information and communication technologies (ICTs) now form part of virtually all aspects of our daily lives, including education. However, teacher training in digital competence has been pushed into the background, especially in social sciences and in history instruction, in which digitalization and the use of ICTs is an opportunity for improvement and educational innovation. Consequently, proposals integrating the various types of knowledge into the training of history teachers are still rare and scarce. To solve this problem, this study presents a mixed quantitative and qualitative analysis using a pre- and posttest questionnaire with a sample of 235 students of the primary education degree at the Public University of Navarre who took part in an innovative didactic proposal that was implemented using the technological pedagogical content knowledge (TPACK) model based on digitized primary sources in three resources: PARES (Spanish Archive Portal), EUROPEANA, and BNE (National Library of Spain). The primary aim of this study was for preservice teachers to develop digital competence in teaching social sciences by integrating the technological, pedagogical and content knowledge types using the TPACK model. There were three specific objectives. The first was analyzing the digital knowledge of students following a primary education degree concerning the use of ICTs in history instruction. The second was implementing a didactic proposal in the teaching social sciences course based on the TPACK model by integrating ICTs and history instruction using Spanish and European digitized primary historical sources. Finally, the third was evaluating the impact of this didactic proposal on developing the knowledge types linked to the TPACK model, especially content knowledge (CK) and its technological content knowledge (TCK) and pedagogical content knowledge (PCK) combinations.